Adaptive Fractional Order PI_D_ Control for Multi-Configuration Tank Process (MCTP) Toolbox - Arjin Numsomran; Thanit Trisuwannawat; Vittaya Tipsuwanporn (My University, 2018)
This paper presents an adaptive fractional order PI λ D μ control for multi-configuration tank process (MCTP) toolbox which aims at demonstrating the problem of reference tracking and cross coupling rejection in multi-input-multi-output system.Moreover, we investigate the cases where the system is in the mode of minimum phase and non-minimum phase configuration.Besides providing theoretical control system analysis and design, we develop the multi-configuration tank process software toolbox for providing the non-linear functions of dynamic models of multi-configuration tank process which is the advantage tool for investigating the performances of the controllers.The software toolbox is developed from discrete state P-file S-function which is operated within the MATLAB environment for providing many non-linear functions of dynamic models of multi-configuration tank process such as multi-input multi-output quadruple tank full-interacting process, multi-input multi-output quadruple tank process, multi-input single-output triple tank interacting process, multi-input multi-output coupled tank interacting process.All actual process attributes are encapsulated in S-function as the input parameters, thus the multi-tank function block can be simply adjusted by specifying the physical properties of the tank system.The study explains about the mathematical model of multi-configuration tank process, nonlinear dynamic characteristic, minimum phase and non-minimum phase configuration, software toolbox features and also describes the design of the adaptive fractional order PI λ D μ controller including the performance validation.The results have been illustrated that the proposed controller design scheme can provide the sufficient effectiveness in the performance, stability and robustness.Furthermore, these tests reinforce the usefulness of MCTP toolbox as a complete simulation tool for users to perform an engineering research of multi-configuration tank control system analysis and design, moreover, it contains very useful for validating the control algorithm of multi-input-multi-output system.
Keywords: Toolbox; Advanced Control Systems Design